Potential effect of porcine follicular fluid (pFF) from small-, medium-, and large-sized ovarian follicles on HeLa cell line viability - Youngsabanant, Mayuva; Rabiab , Suphaphorn (Science, Engineering and Health Studies, 2020)
The experiments reported herein show the effect of porcine follicular fluid (pFF) at concentrations of 2, 4, 20, 40, 200, 400, 500, and 600 µg protein/mL on HeLa cell line viability. We found that 600, 500, and 400 µg proteins/mL of pFF from small-, medium-, and large-sized ovarian follicles showed the highest viability (141.65±26.07, 153.14±16.58, and 140.52±11.71%), which was significantly different from the control group (p<0.05), but lower than the positive control. The cell morphology of those cultured in pFF from the medium- and large-sized follicles remained normal. Cell morphology tended to be abnormal at high concentrations of pFF from small-sized ovarian follicles. Thus, we suggest the applicability of pFF from medium- and large-sized ovarian follicles at concentrations of 40, 200, 400, 500, and 600 µg protein/mL as a substitute for heat-treated fetal bovine serum (HTFBS), which is more expensive. However, it should be noted that not only did pFF extracted from small-sized ovarian follicles have no significant effect on the viability of HeLa cell lines; cell morphology tended to be abnormal at high concentrations of pFF. This study contributes to biotechnology research by discovering applications of pFF extracted from ovarian follicles of different sizes as supplements in culture media.